FACTORS AFFECTING STUDENTS INTEREST IN BECOMING PUBLIC ACCOUNTANTS - Lande, Adriani; Irawan , Mohamad Rizal Nur; Syaikhudin, Ahmad Yani (PT. Antis International Publisher, 2024)
This study aims to examine the influence of labor market considerations, financial rewards, and professional risks on accounting students' interest in pursuing a career as public accountants at the Islamic University of Darul Ulum Lamongan and STIE Cendekia Bojonegoro. Methods: The research employed a quantitative associative approach, using a saturated sampling technique, with a sample of 71 final-year accounting students. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS Version 25. Results: The findings reveal that labor market considerations, financial rewards, and professional risks each have a significant positive effect on students' interest in becoming public accountants, with t-test results indicating strong statistical support for all three variables. Simultaneously, these factors collectively influence students' career interests, highlighting their complementary role in shaping aspirations. Novelty: This study underscores the significance of professional risks as a motivating factor, demonstrating that perceived risks, when associated with high potential rewards, can positively influence career decisions. This insight provides a nuanced understanding of the factors driving career preferences among accounting students in Indonesia, with implications for educational institutions and professional organizations aiming to enhance interest in the public accounting profession.